Small livestock production in two villages in the forest and derived savanna zones of southwest Nigeria - Fricke, W. (1979)
Reports on a study of northern Nigeria's ecological conditions and socio-geographical differentiations in relation to cattle husbandry. The book consists of ten main parts. Topical discussions on: Regional differentiation of the natural potential on the basis of physical-geographical factors; general anthropo-geographical basis of agriculture; cattle breeds and the cult and social roots of cattle husbandry; the socio-agrarian forms of cattle husbandry; the classification of cattle husbandry according to socio-economic criteria; the structure of cattle husbandry in important agricultural regions and improvement possibilities; and synthetic view of cattle economy. Recommendations for the improvement of cattle husbandry in Northern Nigeria, bibliography and photographs included at the end.